2008
DOI: 10.1017/s0021859608008101
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the lactation curve of dairy cows using the differentials of growth functions

Abstract: SU MMARYDescriptions of entire lactations were investigated using six mathematical equations, comprising the differentials of four growth functions (logistic, Gompertz, Schumacher and Morgan) and two other equations (Wood and Dijkstra). The data contained monthly milk yield records from 70 first, 70 second and 75 third parity Iranian Holstein cows. Indicators of fit were model behaviour, statistical evaluation and biologically meaningful parameter estimates and lactation features. Analysis of variance with equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 18 publications
6
23
2
1
Order By: Relevance
“…Macciotta et al (2005), Třináctý et al (1990) and Dematawewa et al (2007) presented lower values of the parameters, while Gołębiewski et al (2011) found higher values (except for c). Fathi Nasri et al (2008) observed that the first-parity cows reached the peak yield of 33.6 kg 63 days post-partum, the second-parity cows achieve the climax of 39.5 kg 46 days post-partum and the third-parity cows produced a maximum of 41.8 kg of milk 42 days post-partum. Similarly to Fathi Nasri et al (2008), we also found that later-parity cows reached maximum sooner and produced more milk at peak than younger cows.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Macciotta et al (2005), Třináctý et al (1990) and Dematawewa et al (2007) presented lower values of the parameters, while Gołębiewski et al (2011) found higher values (except for c). Fathi Nasri et al (2008) observed that the first-parity cows reached the peak yield of 33.6 kg 63 days post-partum, the second-parity cows achieve the climax of 39.5 kg 46 days post-partum and the third-parity cows produced a maximum of 41.8 kg of milk 42 days post-partum. Similarly to Fathi Nasri et al (2008), we also found that later-parity cows reached maximum sooner and produced more milk at peak than younger cows.…”
Section: Resultsmentioning
confidence: 99%
“…Fathi Nasri et al (2008) observed that the first-parity cows reached the peak yield of 33.6 kg 63 days post-partum, the second-parity cows achieve the climax of 39.5 kg 46 days post-partum and the third-parity cows produced a maximum of 41.8 kg of milk 42 days post-partum. Similarly to Fathi Nasri et al (2008), we also found that later-parity cows reached maximum sooner and produced more milk at peak than younger cows. In the study of Dematawewa et al (2007) cows produced a maximum of 33.35 kg milk 102 days post-partum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (e.g. Macciotta et al 2005;Fathi Nasri et al 2008), have shown that the differences in the general shape and the differences of model parameters are associated with yield at the beginning of lactation, the degree of incline and decline before and after peak yield, days in milk at peak and peak and lactation yields of the lactation curves.…”
Section: Shape Of the Lactation Curvesmentioning
confidence: 99%